Peran Strategis PPID KPU Kota Palangkaraya dalam Mendukung Demokrasi dan Partisipasi Publik - Veny Nisratul Husna; Kamelia Kamelia; Anisa Anisa; M. Gilang Maulana; M. Sulaiman; Adied Najiyurrahman (Jurnal Kemitraan Masyarakat, 2025)
This study aims to analyze the strategic role of the Information and Documentation Management Officer (PPID) of the General Elections Commission (KPU) of Palangka Raya City in supporting the strengthening of democracy and public participation at the local level. This research uses a qualitative approach with a descriptive-analytical design through documentary studies on regulations, internal policies of KPU, PPID service reports, and public information request data, enriched with observations of the information service mechanisms both offline and online. The results show that, normatively and structurally, the PPID of Palangka Raya City KPU has carried out its functions in accordance with the provisions of Law No. 14 of 2008 and KPU Regulation No. 22 of 2023. The information service procedures, response time limits, and the use of the E-PPID system reflect the institutional commitment to the principle of transparency. However, the level of utilization of public information services is still relatively low and dominated by the academic community, particularly students. Additionally, there have been no recorded requests for information from disabled groups, despite the provision of disability-friendly facilities. These findings indicate a gap between administrative information openness and substantive public participation. This study concludes that strengthening the role of PPID in the future should be directed toward public communication strategies, political education, and inclusive approaches so that information openness does not stop at regulatory compliance but can make a tangible contribution to the consolidation of a participatory and just local democracy.